2014
DOI: 10.1016/j.nicl.2014.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Temporal-lobe morphology differs between healthy adolescents and those with early-onset of depression

Abstract: Major depressive disorder (MDD) has previously been linked to structural changes in several brain regions, particularly in the medial temporal lobes (Bellani, Baiano, Brambilla, 2010; Bellani, Baiano, Brambilla, 2011). This has been determined using voxel-based morphometry, segmentation algorithms, and analysis of shape deformations (Bell-McGinty et al., 2002; Bergouignan et al., 2009; Posener et al., 2003; Vasic et al., 2008; Zhao et al., 2008): these are methods in which information related to the shape and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 73 publications
3
19
0
Order By: Relevance
“…The HF changes in volume were also seen in patients with cognitive impairment, including those with Alzheimer's disease [1,46]. Reduction in the HF volume was observed in heavy cannabis use, in epilepsy, mild cognitive decline, dementia, major depression, the aged, traumatic brain injury, posttraumatic stress disorder, chronic alcoholism, borderline and antisocial personality disorders, obsessive-compulsive disorder, herpes simplex encephalitis, Parkinson's and Huntington's disease, Down's and Turner's syndrome, cardiac arrest, and Cushing's disease [1,10,14,38,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HF changes in volume were also seen in patients with cognitive impairment, including those with Alzheimer's disease [1,46]. Reduction in the HF volume was observed in heavy cannabis use, in epilepsy, mild cognitive decline, dementia, major depression, the aged, traumatic brain injury, posttraumatic stress disorder, chronic alcoholism, borderline and antisocial personality disorders, obsessive-compulsive disorder, herpes simplex encephalitis, Parkinson's and Huntington's disease, Down's and Turner's syndrome, cardiac arrest, and Cushing's disease [1,10,14,38,42].…”
Section: Discussionmentioning
confidence: 99%
“…Malformation, disorder or damage of the HF have a great importance in the pathogenesis, or consequences, of the variety of the neurological and psychiatric disorders, e.g. the epilepsy, schizophrenia, amnesia, depression, anxiety, posttraumatic stress, aging, Alzheimer's and Parkinson's disease [14,26,37,38,41,42,49]. Even the slightest volume changes, which can be identified by modern imaging techniques, may indicate certain neuropathology or pathophysiology in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Further, patients in a current episode of MDD had lower left hippocampal volumes in comparison to controls, whereas patients in remission ( Hawley et al, 2002 ) from MDD showed no reduction in hippocampal volume. In our previous study ( Ramezani et al, 2014 ), we used multi-object statistical pose and shape analysis, and demonstrated brain morphological differences between adolescents with early-onset MDD and healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Volumes of the left parahippocampal gyrus and the left superior temporal gyrus were significantly greater in depressed people compared with controls. 8 In addition, differences in the shape of several structures -particularly the left hippocampus, and the left and right parahippocampal gyri -emerged between depressed patients and controls. The pose (size, anatomical position and orientation) of, in particular, the left and right putamina, right hippocampus, and the left and right inferior temporal gyri also differed between patients with depression and controls.…”
mentioning
confidence: 99%
“…So the changes are unlikely to result from antidepressants. 8 Furthermore, deterioration of executive functions mediated by the frontal lobes may contribute to the intrusive ruminations and OAM endured by people with depression. In people with recurrent depression, frontal dysfunction may undermine their ability to inhibit unpleasant recollections and thought as well as impairing working memory, verbal fluency and cognitive elasticity.…”
mentioning
confidence: 99%